Winning with Pinning: Enhancing Health and Physical Education with Pinterest. Issue 5 (13th June 2017) - Franks, Hillary; Krause, Jennifer M.
Abstract : Social media can enhance teaching and learning by contributing to a quality health and physical education (HPE) program. Social networking has equipped HPE teachers with many novel resources for use in their classrooms. Pinterest (www.pinterest.com ) is a social media website that allows teachers to search and find lesson ideas and professional development opportunities, collaborate and network with other professionals, share resources with students, and provide a platform for family and community involvement. This article presents an overview of the use of Pinterest for HPE teachers.